Using Componential Analysis to Evaluate Translation Results - Sri Dewiyanti; Hani Suryani (Jurnal Bahasa Inggris Terapan, 2017)
Componential analysis is an analysis of the meaning of a word by breaking down the word into different pieces called 'component parts'. This kind of analysis could be helpful in the process of translation to choose the most accurate and closest lexical equivalents. This study aims to weigh the use of componential analysis for evaluating the accuracy of the translated words. The data are five Indonesian dish names and their English translation printed on the packaging of instant spices. The study proves that by using componential analysis inappropriate translation techniques can be identified and better techniques can be decided to produce more accurate translated words, and some possible translation for each cultural word can be produced. Key Words: cultural words, translation techniques, component analysis, Indonesian dish       names